2014
DOI: 10.1155/2014/921364
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Modified Polak-Ribière-Polyak Conjugate Gradient Method to Linear Equality Constraints Minimization Problems

Abstract: Combining the Rosen gradient projection method with the two-term Polak-Ribière-Polyak (PRP) conjugate gradient method, we propose a two-term Polak-Ribière-Polyak (PRP) conjugate gradient projection method for solving linear equality constraints optimization problems. The proposed method possesses some attractive properties: (1) search direction generated by the proposed method is a feasible descent direction; consequently the generated iterates are feasible points; (2) the sequences of function are decreasing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Under some suitable conditions, the global convergence was proved independent on the line search rules. Furthermore, the rate of convergence was improved by the algorithm …”
Section: Optimal Robust Controller and Finite‐time Stabilitymentioning
confidence: 99%
“…Under some suitable conditions, the global convergence was proved independent on the line search rules. Furthermore, the rate of convergence was improved by the algorithm …”
Section: Optimal Robust Controller and Finite‐time Stabilitymentioning
confidence: 99%
“…It is demonstrated that the active set can be seen as the equality constraints of (7), and according to Rosen's gradient projection method (Rosen, 1960 ; Dai, 2014 ), an active set projection matrix is given as follows:…”
Section: Projected Active Set Conjugate Gradient Algorithm For Nonmentioning
confidence: 99%
“…Some modified conjugate gradient methods, which consider the constrained conditions, were thus proposed by modifying the search direction and a projected operator (Dai, 2014 ; Sun et al, 2018 ). Besides, a projected gradient method, which projected the gradient into the feasible region, was proposed by Rosen ( 1960 ), and some modified conjugate gradient methods were extended by some researchers based on the mentioned methods (Li and Li, 2013 ; Dai, 2014 ). Those modified conjugate gradient methods were also applied in optimal robust controllers and robots (Sun et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%